About the use of Interactive Electronic Technical Manuals for the Machine Builder. (2015) - Tuktamyshev, V.R.; Glukhov, D.A.; Kataev, Ya.A.
Abstract: The support of complete product life cycle (PLC) of mechanical facilities is very important. The consumer is a full participant in the PLC stages of the operation, so the producer is obliged to ensure his exploitative documents. The problems of ensuring PLC support of the operation stage - the complexity of perception, development and support of exploitative documents in a paper form is represented. The experience of domestic enterprises to develop interactive electronic technical manuals (IETM) is given. The tool for creating and managing IETM and the way of solving problems that arise in the creation and use of interactive electronic documents is proposed.